Ionic Liquids: Potential Materials for Carbon Dioxide Capture and Utilization - Shukla, Shashi Kant; Khokarale, Santosh G.; Bui, Thai Q.; Mikkola, Jyri-Pekka T. (Frontiers in Materials, 2019)
The nonvolatility, structure-tunability and high CO2 uptake capacity render ionic liquids (ILs) the most exciting materials for the carbon dioxide (CO2) capture and fixation to value-added chemicals. The aim of this mini-review is to give a brief idea about the development of the potential ILs for CO2 capture, the mechanism involved in the CO2 binding and the application of ILs in the conversion of CO2 to useful chemicals. The mechanisms and nature of interactions in between IL-CO2 have been discussed in terms of the nature of cation, anion, presence of functional group and the extent of interaction between the components of ILs. The fixation of CO2 to linear and cyclic carbonates and electroreduction of CO2 to carbon-rich fuels in ILs has been accounted in detail. At the end, future challenges in terms of commercializing the ILs for CO2 capture and utilization technology are discussed.